Педагогічні умови формування толерантності у майбутніх психологів у вищих навчальних закладах - Романовський, Олександр Георгійович (НТУ "ХПI", 2010)
The concept of tolerance, and also meaningfulness of tolerance, is analysed in the article as to the making professional competence of psychologist. The basic pedagogical terms of forming of tolerance are certain for future psychologists in the process of teaching in higher educational establishments.
Keywords: аналіз; сучасна освіта; професійна діяльність